Hundred years of Bangabhaban, 1905-2005. - Baṅgabhabana (Dhaka, Bangladesh). Press Wing. (Dhaka : Press Wing Bangabhaban, 2006)
Articles on the history of Baṅgabhabana, the ofiice and official residence of the president of Bangladesh at the capital, Dhaka.
Includes bibliographical references and index.
Donated By Akbar Ali Khan
Keywords: Baṅgabhabana (Dhaka, Bangladesh) -- History; Presidents -- Dwellings -- Bangladesh -- Dhaka -- History -- 20th century; Dhaka (Bangladesh) -- Buildings, structures, etc